2001
DOI: 10.1046/j.1365-2435.2001.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the net ecosystem CO2 exchange of a mature Amazonian transitional tropical forest (cerradão)

Abstract: Summary 1.Tower-based eddy covariance and measurements of the vertical CO 2 concentration gradient within the canopy were used to quantify the seasonal variations in the net ecosystem CO 2 exchange ( NEE ) of a 28 -30 m tall transitional tropical forest (cerradão). The study was conducted near the city of Sinop, Mato Grosso, Brazil (11 ° 24·75 ′ S; 55 ° 19·50 ′ W), which is located in the ecotone of two major regional ecosystem types of South America (tropical rainforest and savanna). 2. The NEE during the dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 46 publications
5
89
0
9
Order By: Relevance
“…Similarly, Vourlitis et al (2002) suggest a Cerradão site was also in balance after measurements between August 1999 and July 2001. It seems worthwhile to mention those authors report a very small difference between gross ecosystem exchange -1 and ecosystem respiration, that is, 0.05 tC ha , which ultimately means a weak although significant sink exists.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Similarly, Vourlitis et al (2002) suggest a Cerradão site was also in balance after measurements between August 1999 and July 2001. It seems worthwhile to mention those authors report a very small difference between gross ecosystem exchange -1 and ecosystem respiration, that is, 0.05 tC ha , which ultimately means a weak although significant sink exists.…”
Section: Discussionmentioning
confidence: 83%
“…Several experimental studies have adressed the carbon exchange using automatic monitoring in the Amazon rain forests as part of the LBA Project (LBA 1996;Grace et al 1996, Malhi et al 1998. Pioneer studies in Brazillian savanna were reported by Miranda et al (1997) in a Cerrado Sensu stricto in the central region, and by Vourlitis et al (2001) in a Cerradão vegetation at the ecotone between tropical savanna and rain forest in Central Brasil. Related investigations in South America about water cycle and carbon stocks in tropical savanna were developed in Venezuela (San Jose et al 2001;Szarzynsky and Anhuf et al 1999).…”
Section: Introductionmentioning
confidence: 94%
“…Thereby, for a given ecosystem when the vegetation growth is limited, the AR may be also expected to be limited and leads, therefore, to a significant reduction of the ER. This was probably the case for the savannah site during the dry periods with the ER value remarkably lower than that of the forest, the HR resulting mainly from the dissolved organic carbon or stimulation of the microorganism activities of the soil, surface litter amount, and soil organic matter pool (Vourlitis et al 2001;Davidson et al 2006a;Williams et al 2009). Fig.…”
Section: Larger Ecosystem Respiration (Er) For the Forest Than Savannahmentioning
confidence: 95%
“…The average of the CO 2 nighttime fluxes reported for the tropical forests and woodlands ranged from 3 to 8.5 μmol m −2 s −1 , with little seasonal variability (Vourlitis et al 2001;Loescher et al 2003;Merbold et al 2009;Longdoz et al 2010;Ago et al 2015). It varied between 1 and 6 μmol m −2 s −1 for the savannah sites in West Africa (Brümmer et al 2008;Merbold et al 2009;Ago et al 2014;Tagesson et al 2015; Quansah .…”
Section: Larger Ecosystem Respiration (Er) For the Forest Than Savannahmentioning
confidence: 98%
“…It provides a unique contribution to the study of the environmental, biological and climatological controls of net surface exchange between vegetation and the atmosphere [4][5][6][7][8] . However, eddy covariance technique is limited to use and easily related to measurement errors by many factors, such as vegetation height, footprint area, boundary-layer stability, sensor heights and separation, frequency response, alignment problems, and interference from tower or instrument-mounting structures.…”
mentioning
confidence: 99%